Scintillating properties of gallogermanate glass scintillators doped with Tb3+/Eu3+. Issue 6 (15th March 2023) - Huang, WenJun; Li, Yi; Chen, JunYu; Zhao, YuFan; Chen, LiPing; Guo, Hai
Abstract: Compared with single-crystal scintillator, the glass scintillators have the benefits of low cost, big size, straightforward manufacturing method, and adjustable component. In this work, a succession of diaphanous gallogermanate glass scintillators doped with Tb 3+ or Eu 3+ were manufactured using melt-quenching technique. The thermal, structural, photoluminescent, and scintillating properties were studied. For photoluminescent properties, 12 mol% Tb 3+ -doped glass sample has high internal quantum efficiency (87.8%) and no obvious concentration quenching phenomenon can be observed. For scintillating properties, the optimal doping concentration of Tb 3+ and Eu 3+ are 4 mol% and 8 mol%, respectively. The integral intensity of X-ray excited luminescence of Tb 3+ -doped sample is 73.1% of that of Bi4 Ge3 O12 scintillator, while the ratio of Eu 3+ -doped sample is 26.5%. The radiation damage of 4 mol% Tb 3+ -doped sample resulted by high power X-ray could be repaired through heat-treatment, while 8 mol% Eu 3+ -doped sample exhibits fine stability that the transmittance keeps constant after exposed to high power X-ray. Our research indicates Tb 3+ or Eu 3+ doped gallogermanate glass might be candidate for X-ray detection of slow events.